A STUDY ON MAIL MANAGEMENT OPTIMIZATION THROUGH THE SENAPATI APPLICATION IN ELECTION ORGANIZATIONS - Melodi, Praditha Salwa; Marsofiyati; Wolor, Christian Wiradendi (Jurnal Pendidikan Ekonomi, Perkantoran, dan Akuntansi, 2024)
Effective and efficient mail management is an important aspect for the General Election Commission of the Republic of Indonesia (KPU) in carrying out its duties. This study aims to understand the effectiveness and sustainability of incoming and outgoing mail management through the Senapati system at the Depok City General Election Commissions. This study uses a qualitative method with data collection techniques through in-depth interviews, observations, and document analysis. Testing the validity of data using the source triangulation method. This study shows that the Senapati application has proven effective in increasing the effectiveness of incoming and outgoing mail management at the Depok City General Election Commissions. This is evidenced by the reduced time to process letters, increased accuracy of letter data, and increased user satisfaction. However, the sustainability of the Senapati application management still needs to be improved. This study contributes to providing an understanding of the effectiveness and sustainability of incoming and outgoing mail management through the Senapati system at the Depok City General Election Commissions.